Capital Subsidies Implicit in Concessional Finance : How to Make Them More Transparent and Better Targeted - Kingdom, William; Baeumler, Axel; Guzman, Alfonso (World Bank, Washington, DC, 2013)
Multilateral Development Banks (MDBs) finance a significant share of developing country water sector investments in Vietnam. Much of this financing is concessional and often on-lent by national governments, at similar concessional terms, to water utilities. This concessionality carries an implicit subsidy, i.e., the difference between MDB financing terms and commercial financing terms priced more in line with the underlying credit risks. As such concessional financing is most often used for capital investment projects, the implicit subsidy can be considered a capital subsidy. This working paper asks whether there is an opportunity to increase the value of concessional financing for water sector investments by making implicit capital subsidies more explicit and targeting them to a clearly defined public policy objective. Specifically, the paper (i) considers the extent to which implicit subsidies exist in MDB lending for the water sector; (ii) identifies a possible approach to quantify the amount of subsidies involved; (iii) outlines an emerging framework to make subsidies more explicit as a basis for improved targeting; and (iv) discusses operational implications. By investigating these issues, the paper intends to be a first step for governments and donors to evaluate how best to use the implicit capital subsidies provided by concessional financing in the water sector. The paper also suggests areas of future research.